(untitled) - Dr. Vo Van Dung (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
When human feel powerless towards the context of a volatile society and constant war, they fall into misery. However, the outlook on life in Zhuangzi’s philosophical ideology not only has unique value in terms of history, culture, ideology of ancient China society, but also has a great influence on current society. This article focuses on researching on the inheritance and basic contents as well as gives an assessment on the outlook on life and the world in Zhuangzi’s philosophical thought, also showing the limitations of the article to make some recommendations for other scientists in their next study.